OPTIMASI ADSORPSI Cr(VI) PADA SILIKA GEL DARI ABU SEKAM PADI TERMODIFIKASI DIFENILKARBAZIDA (Si-DPZida) - Henny Puspa Dewi Giri; I Wayan Sudiarta; Ida Ayu Raka Astiti Asih (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2014)
Adsorption of chromium (VI) on silica gel modified by diphenilcarbazide (Si-DPZida) have been studied. Parameters analyzed were surface acidity by acid-base titration method, specific surface area by absorption of methylene blue method, optimum conditions of adsorption (pH, contact time), and isotherm adsorption. The results showed that Si-DPZida adsorbent has surface acidity (Kal) of 1,5996 mmol/g with the number of active sites of 9,6328 x 1020 atom/g with specific surface area of 4.4538 m2/g. The optimum adsorption process of chromium (VI) by both Si-DPZida occurred at pH 5 and 15 minutes of contact time. The isotherm adsorptions on both adsorbents tend to follow Freundlich adsorption pattern.